2021
DOI: 10.1002/anie.202103058
|View full text |Cite
|
Sign up to set email alerts
|

Trimetallic Spinel NiCo2−xFexO4 Nanoboxes for Highly Efficient Electrocatalytic Oxygen Evolution

Abstract: The development of efficient and low‐cost electrocatalysts toward the oxygen evolution reaction (OER) is critical for improving the efficiency of several electrochemical energy conversion and storage devices. Here, we report an elaborate design and synthesis of porous Co‐based trimetallic spinel oxide nanoboxes (NiCo2−xFexO4 NBs) by a novel metal‐organic framework engaged strategy, which involves chemical etching, cation exchange, and subsequent thermal oxidation processes. Owing to the structural and composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
167
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(184 citation statements)
references
References 54 publications
(54 reference statements)
4
167
0
Order By: Relevance
“…MOFs are crystalline materials with an ordered topological structure that are often used as template for the engineering of porous nanostructured electrocatalysts. 49–51 We combined this approach with the hydrolysis of an ammonium salt and the simultaneous MOF etching to prepare Mo–Co-based porous materials. A scheme of the synthesis process is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MOFs are crystalline materials with an ordered topological structure that are often used as template for the engineering of porous nanostructured electrocatalysts. 49–51 We combined this approach with the hydrolysis of an ammonium salt and the simultaneous MOF etching to prepare Mo–Co-based porous materials. A scheme of the synthesis process is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…32–34 Compared to the pure TA, the peak intensity of C–OH stretching at 1027 cm −1 decreased, the peak intensity of asymmetric R–O–R′ stretching at 1115 cm −1 increased, and the red shift of the specific broad O–H band at 3390 cm −1 occurred, and a characteristic peak at 1384 cm −1 also appeared in TA–Fe and TA–Fe–PI attributed to the Fe–O band, suggesting that TA could also be used for chelating with ferric ions. 35,36 Therefore, it could be concluded that the TA–Fe–PI composite had been successfully prepared.…”
Section: Resultsmentioning
confidence: 95%
“…Meanwhile, the Raman spectrum of P-HEOs shows three features of E g (350 cm À1 ), F 2g (515 cm À1 ), and A 1g (675 cm À1 ) attributed to the characteristic vibrational modes of Fd-3 m space group (Figure 1 d). [22,38] It should be noted that the entropy-stabilized oxides contain Fe, Cr, Co, Ni, and Cu elements and their molar ratios are approximately 1: 1: 1: 1: 1, which is confirmed by energy dispersive X-ray (EDX) spectroscopy and inductively coupled plasma optical emission spectroscopy (ICP-OES) (Figure S1, Table S1 and S2). These results jointly validate that we have successfully synthesized spinel HEOs by the low-temperature plasma strategy.…”
mentioning
confidence: 71%